Enabling Self-Organization in Embedded Systems with Reconfigurable Hardware. (20th August 2009) - Bobda, Christophe; Cheng, Kevin; Mühlbauer, Felix; Drechsler, Klaus; Schulte, Jan; Murr, Dominik; Tanougast, Camel
Abstract : We present a methodology based on self-organization to manage resources in networked embedded systems based on reconfigurable hardware. Two points are detailed in this paper, the monitoring system used to analyse the system and the Local Marketplaces Global Symbiosis (LMGS) concept defined for self-organization of dynamically reconfigurable nodes.